PERANAN AKUN RESMI DALAM MEMBENTUK STRATEGI TOTAL RELATIONSHIP MARKETING INDUSTRI RITEL DI INDONESIA - SIANDY, SURYA (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Total Relationship Marketing is a marketing based on relationships, network, and interactions. The goal is to integrate the relationship patterns in relationship marketing as a whole and to complete it. Total Relationship Marketing also lead to a mutually long term beneficial relationship between consumers and third parties, in which the corporate values were founded between stakeholders. The implementation of Total Relationship Marketing in information technology made by using the official account which provided in social networking site membership services. The success of social network site in developing web-based community provides benefits for retailers to develop a more specific approach in building relationships with customers. This was in line with the core values in Total Relationship Marketing. Based on the observations of the author, it is known that most retailers in Indonesia has utilized the official account with different intensity level and ways. Promotional activities, information given, and respond to customer complaints are activities that most often done by retailers in managing their official account. Social networking sites that most widely used wasFacebook and Twitter.